ANALISIS SPASIAL DAYA DUKUNG DAN DAYA TAMPUNG PANGAN KOTA DEPOK - Resa Ana Dina; Eka Purna Yudha (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
Carrying capacity and capacity are environmental conditions so that they can still support the activities of the people who live in them. Development that is not planned and does not pay attention to the environment is a triggering factor for the environment. Therefore, various efforts are needed to improve food availability in urban areas, especially Depok City as an alternative source of life. Depok City is in a very strategic geographical position, including the Jabodetabekpunjur metropolitan area. Food carrying capacity and capacity in the city of Depok can be an alternative plan for life.